2023
DOI: 10.1159/000532043
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Adherence to Therapy, Treatment Acceptability, and Clinical Outcomes in Adults with Attention-Deficit/Hyperactivity Disorder: Results from the COMPAS Multicenter Randomized Controlled Trial

Carlos López-Pinar,
Helena Rosen,
Benjamin Selaskowski
et al.

Abstract: <b><i>Introduction:</i></b> Cognitive behavioral therapy and dialectical behavior therapy (DBT) can be effective in treating adults with ADHD, and patients generally consider these interventions useful. While adherence, as measured by attendance at sessions, is mostly sufficient, adherence to therapy skills has not been assessed. Furthermore, the relationship between patient evaluation of therapy effectiveness, treatment adherence, and clinical outcomes is understudied. <b><i&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Research shows that when CBT is adapted specifically for ADHD symptoms, it can provide concrete strategies for managing the core symptoms of inattention, hyperactivity and impulsivity, and the associated personal interpersonal, social and occupational concomitants of the condition ( 55 ). Additionally, adapted DBT group interventions have demonstrated high effectiveness and acceptability, in helping people manage ADHD related symptoms ( 38 43 ). Group delivery of therapy is not commonplace within NHSTTAD services for patients with higher levels of distress or complexity, with one to one CBT being the primary treatment option.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research shows that when CBT is adapted specifically for ADHD symptoms, it can provide concrete strategies for managing the core symptoms of inattention, hyperactivity and impulsivity, and the associated personal interpersonal, social and occupational concomitants of the condition ( 55 ). Additionally, adapted DBT group interventions have demonstrated high effectiveness and acceptability, in helping people manage ADHD related symptoms ( 38 43 ). Group delivery of therapy is not commonplace within NHSTTAD services for patients with higher levels of distress or complexity, with one to one CBT being the primary treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there are a number of studies which have shown the efficacy and acceptability of adapted Dialectical Behaviour Therapy (DBT) for ADHD patients ( 38 43 ). DBT ( 44 ) is an empirically validated approach for working with distress tolerance and coping behaviours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on CBT have shown that participants who complete the homework assignments show greater improvement than participants who do little or no homework [29][30][31]. An app was developed to facilitate homework compliance, with the assumption that students would rather use an app to complete their homework assignments than to complete them on paper.…”
Section: Feasibility Of Cbt For Adhdmentioning
confidence: 99%